La consommation privée en Belgique - Bruno Eugène; Philippe Jeanfils; Benoît Robert (National Bank of Belgium, 2003)
– This paper analyses the path of private consumption and its main macroeconomic determinants. These are related to the life-cycle approach which helps explaining consumption smoothing. In that respect, it is important to go beyond the simple correlation between current disposable income and consumption to incorporate future income expectations and wealth. As for this latter, the paper also proceeds to a careful description of the mechanisms at work in the wealth effect and of the structure of Belgian households' wealth. Empirically, it is shown that in Belgium human wealth plays a far larger role than financial wealth while the interest rate reflects intertemporal substitution in explaining long-term desired consumption. Variations in these long-term determinants impact only gradually on consumption dynamics, highlighting the fact that changes need to be sustained to have sizeable effects. Finally, in addition to the interest rate, human and financial wealth, the significance of liquidity-constrained consumers and of a confidence indicator are tested. However it does not seem that they exhibit a significant contribution to consumption growth.
Keywords: C67; J21; L22; L62; R15; R34; 330; branch survey; car industry; subcontracting; indirect effects; Privater Konsum; Humankapital; Vermögenseffekt; Zins; Belgien